Review of Simon P. Keefe. 2001. Mozart’s Piano Concertos: Dramatic Dialogue in the Age of Enlightenment. Woodbridge: The Boydell Press - Will, Richard (Current Musicology, 2002)
As Simon P. Keefe’s book begins, the German pedagogue Heinrich Christoph Koch is defending the concerto from his usual authority on aesthetic values, the Allgemeine Theorie der schönen Künste (1771-74) of Johann Georg Sulzer. The Theorie complained that “the concerto appears to have more the purpose of giving a skillful player the opportunity to be heard … than to be used for the rendering of passions,” a stern judgment given Sulzer’s conviction that expressing emotion was tantamount to a moral responsibility in the arts (quoted in Koch 1983:209). Koch countered by imagining soloist and accompaniment as partners in a “passionate dialogue,” in which the soloist “expresses his feelings to the orchestra, and it signals him through short interspersed phrases sometimes approval, sometimes acceptance of his expression … by a concerto I imagine something similar to the tragedy of the ancients, where the actor expressed his feelings not towards the pit, but to the chorus” (quoted in Keefe, 17-18). While not always agreeing that what soloist and orchestra share are feelings, many subsequent writers would echo Koch’s description of the concerto as conversation or drama. No works have been more affected than his ideal, the concertos of Mozart.